The relationship between anemia and quality of life in chronic kidney disease patients undergoing hemodialysis at Royal Prima Hospital - Manalu, Angelia Tesalonika Mawarni; Suhartina, Suhartina; Wienaldi, Wienaldi (Buletin Kedokteran & Kesehatan Prima, 2024)
This study aimed to investigate the relationship between anemia and quality of life in patients with chronic renal failure undergoing hemodialysis at Royal Prima Hospital. An analytical observational design using a cross-sectional approach was used. Data were collected from pre-existing medical records, and quality of life was assessed using a modified WHOQOL-BREF questionnaire that evaluates various aspects of life using a 5-point Likert scale. The chi-square test was used to determine the significance of the relationship between anemia status and quality of life among patients. A study of 51 hemodialysis patients at Royal Prima Hospital showed a high prevalence of anemia, with 86.3% of patients showing hemoglobin levels below the normal range. Although most patients (92.2%) were prescribed Sangobion, an iron supplement, many patients remained anemic, indicating a potential problem in terms of treatment efficacy or compliance. The duration of hemodialysis varied among the participants, with most undergoing treatment for more than 24 months, while the others were on hemodialysis for less than 24 months. About 92.2% reported a moderate quality of life, while only 7.8% experienced a poor quality of life. Statistical analysis showed no significant difference in the quality of life between patients with and without anemia (p=0.495), indicating that anemia may not have a direct impact on the overall quality of life for this patient population. In conclusion, although anemia is prevalent in hemodialysis patients at Royal Prima Hospital, its association with quality of life appears to be limited based on the findings of this study. Future research should focus on understanding the causes of anemia in this population and developing targeted strategies to improve the hematological status and overall quality of life of patients undergoing hemodialysis.